MEMBANGUN RUMAH TANGGA SAKINAH PANDUAN PRAKTIS DARI AL-QUR’AN DAN SUNNAH - Iranti, Meli; Muthi’ah, Muthi’ah; Zahara, Rezi; Binasti, Binasti; Septiani, Eka Zahra; Kartika, Yeni; Yesi, Rahma; Noviani, Dwi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This article explores the importance of building a sakinah (tranquil) household based on the values of the Qur'an and Sunnah as the foundational pillars of Muslim family life. A household is not merely a biological or administrative union, but a spiritual institution aimed at achieving tranquility (sakinah), love (mawaddah), and compassion (rahmah). Using a qualitative method with a literature-based approach, the authors analyze classical and contemporary Islamic sources to offer practical guidance for establishing a harmonious family. The findings reveal that many challenges in modern Muslim families stem from a lack of understanding and application of Islamic values in daily life. Therefore, value education, effective communication, and spiritual awareness are crucial in building a strong family unit emotionally, socially, and religiously. This article aims to make a meaningful contribution to the development of Muslim families and foster a morally upright society guided by divine principles.